A brain atlas of the carrion crow (Corvus corone). Issue 17 (8th August 2022) - Kersten, Ylva; Friedrich‐Müller, Bettina; Nieder, Andreas
Abstract: Corvidae, passerine songbirds such as jays, crows, and ravens known as corvids, have become model systems for the study of avian cognition. The superior cognitive capabilities of corvids mainly emerge from a disproportionally large telencephalon found in these species. However, a systematic mapping of the neuroanatomy of the corvid brain, and the telencephalon in particular, is lacking so far. Here, we present a brain atlas of the carrion crow, Corvus corone, with special emphasis on the telencephalic pallium. We applied four staining techniques to brain slices (Nissl, myelin, combination of Nissl and myelin, and tyrosine hydroxylase targeting catecholaminergic neurons). This allowed us to identify brain nuclei throughout the brain and delineate the known pallial subdivisions termed hyperpallium, entopallium, mesopallium, nidopallium, arcopallium, and hippocampal complex. The extent of these subdivisions and brain nuclei are described according to stereotaxic coordinates. In addition, 3D depictions of pallial regions were reconstructed from these slices. While the overall organization of the carrion crow's brain matches other songbird brains, the relative proportions and expansions of associative pallial areas differ considerably in agreement with enhanced cognitive skills found in corvids. The presented global organization of the crow brain in stereotaxic coordinates will help to guide future neurobiological studies in corvids. Abstract : Kersten et al. present a brain atlas of the carrion crow, Corvus corone, a corvid songbird. Based on different staining techniques applied to brain slices and 3D reconstructions, the global organization of the crow brain is shown in stereotaxic coordinates. This atlas will help to compare avian species and guide future neurobiological studies of corvids.